To multiply the polynomial expressions \( (2x^2 - 3)(x + 5) \), we can use the distributive property (also known as the FOIL method for binomials).
-
Distribute \( 2x^2 \) to both terms in \( (x + 5) \):
- \( 2x^2 \cdot x = 2x^3 \)
- \( 2x^2 \cdot 5 = 10x^2 \)
-
Distribute \( -3 \) to both terms in \( (x + 5) \):
- \( -3 \cdot x = -3x \)
- \( -3 \cdot 5 = -15 \)
Now combine all the terms we obtained: \[ 2x^3 + 10x^2 - 3x - 15 \]
So, the simplified result is: \[ 2x^3 + 10x^2 - 3x - 15 \]
Therefore, the correct response is: 2x^3 + 10x^2 - 3x - 15.